(untitled) - Heldt, Hans-Walter (Oxford, 1999)
This book explains the basic principles of plant metabolism and its many applications in commerce and agriculture, covering photosynthesis, primary and secondary metabolism, the function of phytohormones, and molecular engineering. It includes cel structure and function, glycerolipids, photoassimilation, polysaccharide metabolism, nitrogen fixation, phloem transport, plant storage proteins and protein biosynthesis, natural pesticides, the roles of isoprenoids and phenylpropanoids, plant growth regulation and development, and plant cell genetics and gen technology. The book also describes the many practical commercial applications of plant biochemistry, molecular biology, and biotechnology.
Keywords: Plant physiology